1978
DOI: 10.1002/bjs.1800650502
|View full text |Cite
|
Sign up to set email alerts
|

Causes of failure in the surgical treatment of primary hyperparathyroidism: Lessons from 51 successful reoperations

Abstract: A review of 51 successful reoperations for persisting hypercalcaemia due to primary hyperparathyroidism shows that inadequate anatomical knowledge, inadequate surgical technique and unusual localizations of the parathyroids are the most frequent causes of failure of the primary operation. The majority of these failures are therefore preventable. There is a frequent need for cervical thymectomy in parathyroid surgery. Sternotomy is only very rarely necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1982
1982
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In the vast majority of cases, however, mediastinal parathyroid glands can be resected via a cervical approach. [4][5][6][7][8][9][10] The remaining patients have traditionally been treated with median sternotomy, although thoracotomy, [10][11][12][13] anterior mediastinotomy, 14 transcatheter ablation, 15 and various videoassisted techniques 10,16,17 have also been used.…”
mentioning
confidence: 99%
“…In the vast majority of cases, however, mediastinal parathyroid glands can be resected via a cervical approach. [4][5][6][7][8][9][10] The remaining patients have traditionally been treated with median sternotomy, although thoracotomy, [10][11][12][13] anterior mediastinotomy, 14 transcatheter ablation, 15 and various videoassisted techniques 10,16,17 have also been used.…”
mentioning
confidence: 99%
“…The first large series of mediastinal hyperfunctioning parathyroid tumors was reported by Nathaniels et al in 1970 [1]. From this report and from other surgical papers published subsequently [2][3][4][5][6] as well as from anatomic studies [7][8][9], the following conclusions can be drawn: (a) there is a substantial number of normal parathyroid glands as well as parathyroid tumors located in the mediastinum (2-20%), mostly within or close to the thymus [1,6,[7][8][9]; (b) most mediastinal parathyroid tumors can be removed from the neck mainly by partial or complete cervical thymectomy [10, 11 >; (c) during reoperative surgery most tumors are found in the neck [3][4][5]12 ]; and (d) item (b) is also true for reoperative surgery and only a small percentage of patients (2-22%) require sternotomy [3][4][5].…”
Section: Invited Commentarymentioning
confidence: 65%
“…Edis et al suggested that the reason for the unsuccessful initial exploration is "failure on the part of the surgeon to appreciate the nuances and variations of normal parathyroid anatomy" [13]. This point of view is supported by several reported series of reexploration where the missing gland was subsequently located in a normal anatomical position in up to 60% of cases [7,14,15]. This simple comment, however, understates what most surgeons regard as a complex problem.…”
Section: Casementioning
confidence: 99%